PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ONLINE PENGGUNA APLIKASI SHOPEE MAHASISWA PENDIDIKAN EKONOMI FKIP UNRI - Lili Suriyani; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Internet access that is increasingly developing nowdays caused a change of consumers shopping place in making purchase decisions. This research aims to determine the effect of products, prices and promotions towards online purchasing decisions at Shopee of Economic Education students. The population were students of Economic Education, while the sample were 69 students who had downloaded and shopped at Shopee. The data were collected by using a closed questionnaire which was analyzed by using quantitative techniques with multiple linear regression approaches. The results showed that the products, prices and promotions simultaneously affect the online purchasing decisions of Economic Education students.Key Words: Products, Prices, Promotions and Purchasing Decisions